The effectiveness of DNA databases in relation to their purpose and content : a systematic review - De Moor, Sabine (2019)
Different stakeholders use forensic DNA databases for different purposes; for example, law enforcement agencies use them as an investigative tool to identify suspects, and criminologists use them to study the offending patterns of unidentified suspects. A number of researchers have already studied their effectiveness, but none has performed an overview of the relevant literature. Such an overview could help future researchers and policymakers by evaluating their creation, use and expansion. Using a systematic review, this article synthesizes the most relevant research into the effectiveness of forensic DNA databases published between January 1985 and March 2018. We report the results of the selected studies and look deeper into the evidence by evaluating the relationship between the purpose, content, and effectiveness of DNA databases, three inseparable elements in this type of research. We classify the studies by purposes: (i) detection and clearance; (ii) deterrence; and (iii) criminological scientific knowledge. Each category uses different measurements to evaluate effectiveness. The majority of these studies report positive results, supporting the assumption that DNA databases are an effective tool for the police, society, and criminologists. (C) 2019 Elsevier B.V. All rights reserved